A New Instrument to Assess Children's Understanding of Death: Psychometrical Properties of the EsCoMu Scale in a Sample of Spanish Children - Manuel Fernández-Alcántara; Macarena de los Santos-Roig; María Nieves Pérez-Marfil; Francisco Cruz-Quintana; Juan Manuel Vázquez-Sánchez; Rafael Montoya-Juárez (MDPI AG, 2021)
The acquisition of the death concept in children may influence how these children cope with the losses that they will confront throughout their lives. At the present time, there is a lack of psychometric instruments in Spanish-speaking countries in order to evaluate the components of the death concept in children. The aim of this study was to create and validate a scale (EsCoMu-Escala sobre el Concepto de Muerte) in order to provide insight about the concept of death in children. The sample was formed by 358 children from ages 6 to 13 years. The final EsCoMu version has 27 items which serve to evaluate universality, irreversibility, non-functionality and causality. The results of the confirmatory factor analysis show an adequate fit index for the four dimensions model, reliability (α = 83) and validity evidence, specifically based on the children's age. In conclusion, EsCoMu is an instrument that shows adequate reliability and validity indices in order to assess the concept of death and its four components among children. Due to its simplicity, this instrument can be very useful if applied to the field of neurodevelopmental disorders.